Testing for Behavioral and Physiological Responses of Domestic Horses (Equus caballus) Across Different Contexts – Consistency Over Time and Effects of Context - Safryghin, Alexandra; Hebesberger, Denise V.; Wascher, Claudia A. F. (Frontiers in Psychology, 2019)
In a number of species, consistent behavioral differences between individuals have been described in standardized tests, e.g. novel object exploration, open field test. Different behavioral expressions are reflective of different coping strategies of individuals in stressful situations. A causal link between behavioral responses and the activation of the physiological stress response is assumed but not thoroughly studied. Also, most standard paradigms investigating individual behavioral differences, are framed in a fearful context, therefore the present study aimed to add a test in a more positive context, the feeding context. We assessed individual differences in physiological (heart rate, HR) and behavioral responses (presence or absence of pawing, startle response, defecation, snorting) of twenty domestic horses (Equus caballus) in two behavioral experiments, a novel object presentation and a pre-feeding excitement test. Experiments were conducted twice, once between July and August, and once between September and October. Both experiments caused higher mean HR in the first ten seconds after stimulus presentation compared to a control condition, but mean HR did not differ between the experimental conditions. In the novel object experiment, horses displaying stress-related behaviors during the experiments also showed a significantly higher HR increase compared to horses which did not display any stress-related behaviors, reflecting a correlation between behavioral and physiological responses to the novel object. On the contrary, in the pre-feeding experiments, horses that showed fewer behavioral responses had a greater HR increase, indicating the physiological response being due to emotional arousal and not behavioral activity. Moreover, HR response to experimental situations varied significantly between individuals. Individual average HR was significantly repeatable across both experiments, whereas HR increase was only significantly repeatable during the novel object and not the pre-feeding experiment. Conversely, behavioral response was not repeatable. In conclusion, our findings show that horses’ behavioral and physiological responses differed between test situations and that emotional reactivity, shown via mean HR and HR increase, is not always displayed behaviorally, suggesting that behavioural and physiological responses may be regulated independently according to context.